Cistólitos de representantes da tribo Justicieae (Acanthaceae) do semiárido da Bahia, Brasil - Carneiro, Joseane Silva (2011)
The presence of cystoliths is one of the diagnostic characters of the subtribe Justicieae, one of the largest among the Acanthaceae family. Cystoliths are cellular inclusions composed of calcium carbonate and are often found on idioblastic cells (lithocysts) leaf epidermis. Morphology and distribution of lithocysts are variable among different taxa, is of great importance in taxonomic studies. For this study, we include ten genera of 22 species of subtribe Justicieae (Acanthaceae) that occur in the semiarid region of Bahia. Samples were collected from leaves of the species for the micromorphological study of cystoliths on specimens deposited in the Herbarium of Universidade Estadual de Feira de Santana, when possible two or more specimens were studied. The leaf samples were rehydrated and fixed. Leaf sections were collected for analysis of cystoliths in the epidermis. To check the chemical composition of cystoliths, we dealt with the glacial acetic acid test, obtaining positive results. The metric parameters of cystoliths were obtained by taking 25 random measurements (length and width) and the results submitted to the statistics. All species examined showed lithocysts containing cystoliths with great variation in length, width and shape, which are present in both leaf epidermises. The lithocysts tended to be globoids, big, with primary, thin, cellulosic walls, and without being completely filled by cystoliths. These are sessile, solitary, elliptical, wide or narrow, one or both ends rounded, ornamented with undulating surface, with long, straight axis, but also presenting a few cystoliths curved in all specimens. The species were grouped into three types cystoliths based on morphology: a) cystoliths long and rounded at both ends occurred in ten species; b) cystoliths long, with one rounded end, seen in seven species, c) highly variable cystoliths, observed in five species. The study shows that studied species of Justicieae subtribe can not be segregated themselves by size and shape of cystoliths separately, even to segregate the genera, unless these traits are associated with other characters, since the size and shape of cystolith have great variability, and they may be influenced by environmental factors.